Penerapan Metode Tanya Jawab untuk Meningkatkan Keaktifan dan Hasil Belajar IPS Kelas VIII SMPN 2 Ngantru - Ade Aslama; Anggoro Putranto (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This thesis is motivated by the discovery of several problems. One of them is the lack of innovation from teachers in delivering social studies learning materials. When social studies learning takes place, the teacher only uses the lecture method which is less effective. This makes some students feel bored and sleepy. Therefore, teachers need to make some efforts to make learning better. The purpose of this research is (1) the effectiveness of the application of the question and answer method to increase student activeness in social studies learning class VIII at SMPN 2 Ngantru Tulungagung school year 2023/2024 (2) the effectiveness of the application of the question and answer method to increase student learning outcomes in social studies learning class VIII at SMPN 2 Ngantru school year 2023/2024 (3) the relationship between the application of the question and answer method with student activeness and student learning outcomes in social studies learning class VIII at SMPN 2 Ngantru school year 2023/2024. This research uses a quantitative approach. The study involved a control class and an experimental class. Based on the results of the questionnaire control class and experimental class greater than 0.05 (0.077 > 0.05 and 0.169 > 0.05). So it can be concluded from the data that the student activeness of the control class and the experimental class is homogeneous for the variable application of the question and answer method to student activeness.